Assembly of the aspartate transcarbamoylase holoenzyme from transcriptionally independent catalytic and regulatory cistrons. - Foltermann, K F (1984)
The cistrons encoding the regulatory and catalytic polypeptides of aspartate transcarbamoylase (EC 2.1.3.2) from Escherichia coli K-12 have been cloned separately on plasmids from different incompatability groups. The catalytic cistron (pyrB) was carried by pACYC184 and expressed from its own promoter, whereas the regulatory cistron was expressed from the lac po of pBH20. The catalytic polypeptide chains assembled into enzymatically active trimers (c3) in vivo when expressed in the absence of regulatory subunits. Similarly, the regulatory polypeptide chains assembled into regulatory dimers (r2) in vivo in the absence of catalytic subunits. When cellular extracts containing regulatory dimers and catalytic trimers synthesized in separate cells were combined in vitro, partial spontaneous holoenzyme assembly occurred. When pyrB and pyrI were expressed from transcriptionally independent cistrons in the same cell, all detectable catalytic polypeptides were incorporated into the functional aspartate transcarbamoylase holoenzyme, 2(c3):3(r2). Thus, it is clear that the in vivo assembly of ATCase holoenzyme is a direct, spontaneous process involving the association of preformed regulatory subunits (r2) and catalytic subunits (c3). This procedure provides a general method for the construction of hybrid aspartate transcarbamoylase in vivo and may be applicable to other oligomeric enzymes constructed from different polypeptides.